Abrindo o livro das suas vidas: trajetórias de formação de quatro professoras negras - Santos, Fernanda Gabriela Soares dos (2010)
The research called Opening the book of its lives: formation trajectories of four black teachers were developed and presented to the Program of Post-Graduation in Education, Master of the Center of Education of the Federal University of Santa Maria (UFSM), in the line Formation, to know and Professional Development, having as objective to investigate the personal and professional trajectory of four pertaining black teachers of different generations, as well as its imaginary and possible significances of being a black teacher at distinct moments of the History of Brazil. To this, had been invited four teachers who had studied at different moments and that also had marked my personal and professional history, even so two of them have almost the same age possess a trajectory of very different life. This thematic one was being constructed from my performance as professor of the basic education, my studies on blackness, sort and education, of my participation in a group of research and, over all, from my proper history of life. I found in the autobiographical narrative a promising way to develop this work, since what one searched was an approach of its imaginary ones and its possible fights against the instituted whiteness. The register was carried through by the writing of the half-structuralized interviews and its posterior transcription. Used as benchmarks Bosi (2004), Perrot (1997), Gomes (2009) and Castoriadis (1982). I perceived, in its narratives, many approaches: the fight with the socioeconomic question, the choice for the Teaching, the strong presence of the figure maternal in its lives. Also some divergences had been found, in function even though of the secular line that separates them. Reconstruct the history of black women means looking at the history of gender/ethnicity of those who always stayed on the sidelines of historical processes. I point out that the work, beyond having produced a formation in the collaborators, as told for them, also me auto formation resulted in formation. For all of us its research produced another look on the Teaching, on the questions of blackness, sort and the teachers who we were at the beginning are not the same ones that were formed themselves/self formed. Important to note that their individual stories are also part of the collective history, each respondent brought brands that are part of their individual careers and, concomitantly are similar to the larger issues. The struggle for survival, the question of religion, the imagery of daily life were some categories that appeared on all the voices and the other showing that the singular mark of the generation they belong to, the year they were born, the era in which they lived also Social enrolling in the individual, the memory of the railroad to the oldest contributor, and the issue of racial quotas for the youngest contributor.